1985
DOI: 10.1111/j.1365-2125.1985.tb05099.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of mefloquine in man: lack of effect of mefloquine on antipyrine metabolism.

Abstract: 1 A method is described for the determination of the new antimalarial agent, mefloquine, in plasma and urine. 2 After oral administration of 750 mg mefloquine to six volunteers, absorption was apparently slow, with plasma mefloquine concentrations at 24 h (559 + 181 ng ml-1; mean + s.d.) higher than at 6 h (459 + 166 ng ml-1). The elimination half-life was 373 + 249 h, oral clearance was 5.09 + 2.71 h-1, and apparent volume of distribution was 35.7 ± 30.71 kg-1 (assuming 100% bioavailability). 3 Mefloquine (75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…The pharmacokinetics of racMQ show marked variability of absorption and metabolism between subjects and between ethnic groups. Karbwang et al [1] found plasma concentrations in healthy Thai volunteers to be twice as high as those reported by Riviere et al [2] in healthy Caucasian volunteers. In contrast, a study by Juma et al [3] [2].…”
mentioning
confidence: 53%
“…The pharmacokinetics of racMQ show marked variability of absorption and metabolism between subjects and between ethnic groups. Karbwang et al [1] found plasma concentrations in healthy Thai volunteers to be twice as high as those reported by Riviere et al [2] in healthy Caucasian volunteers. In contrast, a study by Juma et al [3] [2].…”
mentioning
confidence: 53%
“…The HPLC method of Riviere et al (6) was used to assay mefloquine from biological fluid. The within assay coefficient of variation was 3.5% at l00nglml and 2.5% at 500nglml and between assay it was 5.4% at 500nglml and 5.5% at 75Onglml.…”
Section: Methodsmentioning
confidence: 99%
“…; Riviere et al, 1985). For the assay of mefloquine in whole blood the extraction procedure was modified as follows; To samples of blood (1 ml) containing WR 184,806 as internal standard ([±-2,8-bis-trifluoromethyl)-4-[1-hydroxy-3-(Ntertbutylamino)-propyl]quinoline] phosphate; 400 ng) was added acetonitrile (2 ml) followed by vortex mixing for 30 s and centrifugation at 1000 g for 5 min.…”
Section: Discussionmentioning
confidence: 99%
“…After vortex mixing for 15 s the mixture was extracted with dichloromethane (6 ml) and the extracts assayed by h.p.l.c. (Riviere et al, 1985). Standard curves were prepared by adding known quantities of mefloquine (50-1000 ng) to either plasma or whole blood containing internal standard (400 ng).…”
Section: Discussionmentioning
confidence: 99%